Exercise as a therapeutic approach to alleviate diabetic kidney disease: mechanisms, clinical evidence and potential exercise prescriptions - Fan, Rao; Kong, Jianda; Zhang, Jiahao; Zhu, Lei (Frontiers in Medicine, 2024)
Diabetic kidney disease (DKD) is a global and severe complication that imposes a significant burden on individual health, families, and society. Currently, the main treatment approaches for DKD include medication, blood glucose control, protein-restricted diet, and blood pressure management, all of which have certain limitations. Exercise, as a non-pharmacological intervention, has attracted increasing attention. This review introduces the mechanisms and clinical evidence of exercise on DKD, and proposes potential exercise prescriptions. Exercise can improve blood glucose stability related to DKD and the renin-angiotensin-aldosterone system (RAAS), reduce renal oxidative stress and inflammation, enhance the crosstalk between muscle and kidneys, and improve endothelial cell function. These mechanisms contribute to the comprehensive improvement of DKD. Compared to traditional treatment methods, exercise has several advantages, including safety, effectiveness, and no significant side effects. It can be used as an adjunct therapy to medication, blood glucose control, protein-restricted diet, and blood pressure management. Despite the evident benefits of exercise in DKD management, there is still a lack of large-scale, long-term randomized controlled trials to provide more evidence and develop exercise guidelines for DKD. Healthcare professionals should actively encourage exercise in DKD patients and develop personalized exercise plans based on individual circumstances.